A New Hardware Architecture for Fuzzy Logic System Acceleration - Abood, Aumalhuda Gani; Jodha, Mohammed A.; Alwan, Majid A. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
In this work, a new architecture is designed for fuzzy logic system. The proposed architecture is implemented on field programed gate array (FPGA). The hardware designed fuzzy systemimproves the excution speed with very high speed up factor using low cost availble kits such as FPGA. The implementation of the proposed architecture uses very low amount of logic elements and logic array blocks as proven when implementing the proposed architucture on FPGA.